2022
DOI: 10.3390/agriculture12050593
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and Potassium Application Improves Fodder Yield and Quality of Sorghum in Aridisol under Diverse Climatic Conditions

Abstract: Fodder yield and quality must be improved for sustainable livestock production. A lack of or low application of phosphorus (P) and potassium (P) are among the leading constraints of lower fodder yield and quality of sorghum [most cultivated fodder crop during kharif season (crop cultivation in summer and harvesting during winter] in Aridisol of Pakistan. Therefore, this two-year field study evaluated the role of different P and K levels on fodder yield and quality of sorghum cultivar ‘Ijar-2002’ planted in Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In addition to its crucial function in metabolism, P is necessary for development, the production of nuclei, the consumption of starch and sugar, cell division and photosynthesis [17]. After nitrogen, it is rated as one of the two biggest global limiting variables for crop growth and production [18]. Since P is rapidly absorbed or fixed by free lime in some calcareous soils, P nutrition is a key limiting factor for crop productivity on such soils [19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its crucial function in metabolism, P is necessary for development, the production of nuclei, the consumption of starch and sugar, cell division and photosynthesis [17]. After nitrogen, it is rated as one of the two biggest global limiting variables for crop growth and production [18]. Since P is rapidly absorbed or fixed by free lime in some calcareous soils, P nutrition is a key limiting factor for crop productivity on such soils [19].…”
Section: Introductionmentioning
confidence: 99%
“…The height of fodder sorghum increased as a result of nitrogen fertilisation, as nitrogen enhance protein synthesis and consequently vegetative growth which resulted in increasing of photosynthetic rate and stimulated of further growth as stated by Mopagar et al (2023), confirming the results mentioned previously. Due to the enhanced availability of these nutrients in the soil and improved root development, P and K treatments also raised plant height and sorghum's capacity to absorb N, P, and K. In the end, this led to a greater yield (Qamar et al, 2022). These treatments also increased soil fertility, which can result in higher crop yields and higher crop quality.…”
Section: Plant Heightmentioning
confidence: 99%
“…The major causes of low soil fertility are large-scale soil erosion, land degradation and poor soil management. According to (Rehman et al, 2022), application of P and K on Aridisols, significantly improved sorghum fodder yield, which is important for sustainable livestock production. A study that compared the microbial community under a legume (sun hemp) and sorghum, found out that there was higher microbial community under sorghum, which is indicative of the potentials of sorghum to improve soil fertility, if beneficial microorganisms are introduced (Eo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%